Allelopathic and intraspecific growth competition effects establishment of direct sown Miscanthus. Issue 6 (30th March 2020) - Awty‐Carroll, Danny; Hauck, Barbara; Clifton‐Brown, John; Robson, Paul
Abstract: High yielding perennial crops are being developed as a sustainable feedstock for renewable energy and bioproducts. Miscanthus is a leading biomass crop, but most plantations comprise a sterile hybrid Miscanthus  ×  giganteus that is clonally propagated. To develop new varieties across large areas, rhizome cloning is inefficient, time consuming and expensive. Alternative approaches use seed, and in temperate regions, this has been successfully applied by raising seedlings as plug plants in glasshouses before transfer to the field. Direct sowing has yet to be proven commercially viable because poor germination has resulted in inconsistent stand establishment. Oversowing using seed clusters is a common approach to improve the establishment of crops and it was hypothesized that such an approach will improve uniformity of density in early Miscanthus stands and thereby improve yield. Sowing multiple seeds creates potential for new interactions, and we identified at least two inhibitory mechanisms related to seed numbers. Germinating seed produced allelopathic effects on nearby seed thereby inhibiting plant growth. The inhibitory effect of Miscanthus seed on germination percentages was related to seed number within clusters. An extract from germinating Miscanthus seed inhibited the germination of Miscanthus seed. The extract was analysed by HPLC, which identified a complex mixture including several known allelopathic compounds including proanthocyanidins and vanillic acid. There was also evidence of root competition in soil in a controlled environment experiment. When the experiment on competition was replicated at field scale, the establishment rates were much lower and there was evidence of shoot competition. We conclude that the numbers of seed required to ensure an acceptable level of establishment in the field may be economically impractical until other agronomic techniques are included either to reduce the inhibitory effects of higher seed numbers or to reduce oversowing rates. Abstract : Oversowing Miscanthus seed clusters was tested as a means to improve crop establishment. Germinating seed produced allelopathic effects on nearby seed thereby inhibiting plant growth. An extract from germinating Miscanthus seed inhibited germination of Miscanthus seed. The extract was analysed by HPLC, which identified a complex mixture including several known allelopathic compounds. There was also evidence of root competition in soil in a controlled environment experiment. We conclude the numbers of seed required to ensure an acceptable level of establishment in the field may be economically impractical until other agronomic techniques are included either to reduce the inhibitory effects of higher seed numbers or to reduce oversowing rates.